This I Believe - Brabazon, John Theodore Cuthbert Moore-Brabazon, Baron (Tufts Archival Research Center, 2006)
Lord Brabazon describes his beliefs that a divine, omnipotent Jesus is also an individual's personal link to God, that Jesus visited England, that merit should be based on intelligence or character rather than birth, that extraterrestial life does not exist, that humans have and must take responsibility for their free will, and that the English-speaking perspective and moral code is the best yet produced.